2016
DOI: 10.1017/s003329171600101x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal reproduction and its neuroanatomical correlates in adults with attention deficit hyperactivity disorder and their unaffected first-degree relatives

Abstract: Abstract:Abstract Background Little is known about time perception, its putative role as cognitive endophenotype, and its neuroanatomical underpinnings in adults with Attention Deficit Hyperactivity Disorder (ADHD). Methods 20 adults with ADHD, 20 unaffected first degree relatives and 20 typically developing controls matched for age and gender undertook structural magnetic resonance imaging (MRI) scans. Voxel-based morphometry (VBM) with DARTEL was performed to obtain regional grey matter volumes. Temporal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
0
10
1
Order By: Relevance
“…Adults with remitted ADHD showed nearly the same levels of impulsivity as the control group. The results described here are in accordance with Pironti et al (2016), and do not support the idea that impulsive behavior is overexpressed in unaffected relatives of ADHD children. Kim et al (2017) found similar results using a different methodology.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Adults with remitted ADHD showed nearly the same levels of impulsivity as the control group. The results described here are in accordance with Pironti et al (2016), and do not support the idea that impulsive behavior is overexpressed in unaffected relatives of ADHD children. Kim et al (2017) found similar results using a different methodology.…”
Section: Discussioncontrasting
confidence: 55%
“…Pauli-Pottt, Neidhard, Heinzel-Gutenbrunner, and Becker (2014) found that unaffected preschoolers with a positive family history of ADHD presented worse scores in delay aversion tasks. Opposite results were found by Pironti et al (2016), who did not find increased impulsivity in ADHD first-degree relatives, although using a different methodology. To the best of our knowledge, there are no studies exploring impulsivity traits in unaffected ADHD parents.…”
Section: Introductionmentioning
confidence: 61%
“…Investigators have hypothesized that temporal reproduction is a cognitive endophenotype associated with executive dysfunction in ADHD, which might have specific genetic implications [20]. This hypothesis was tested in a small study on adults with ADHD in the United States and individuals with ADHD had difficulties in time estimation and replication tasks when compared with the non-ADHD controls [21]. Also, anatomical differences were noted in structural magnetic resonance imaging (MRI) scans, and there was increased grey matter volume in the cerebellum of the ADHD group [21].…”
Section: Adhd the Perception Of Time And Time Processingmentioning
confidence: 99%
“…This hypothesis was tested in a small study on adults with ADHD in the United States and individuals with ADHD had difficulties in time estimation and replication tasks when compared with the non-ADHD controls [21]. Also, anatomical differences were noted in structural magnetic resonance imaging (MRI) scans, and there was increased grey matter volume in the cerebellum of the ADHD group [21]. These investigators hypothesized that there was a correlation between the cerebral anomalies and differences in the perception of time in the group with ADHD [21].…”
Section: Adhd the Perception Of Time And Time Processingmentioning
confidence: 99%
See 1 more Smart Citation